1979
DOI: 10.1073/pnas.76.11.5460
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactive labeling of M13 coat protein in model membranes by use of a glycolipid probe.

Abstract: Coliphage M13 coat protein in synthetic bilayer membranes was labeled by use of 12,(4-azido-2-nitrophenoxy)stearoyl[I-14Clglucosamine, a photoreactive glycolipid probe that spontaneously inserts into membranes. In this model system, the probe preferentially labeled the proteins over the lipids. Experiments designed to test the probe's restriction to integral membrane proteins revealed that extrinsic proteins as well as external peptide fragments of integral membrane proteins were not accessible to the photogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…In contrast to Hu and Wisnieski [13], we have found that coupling of 12-APS-GA to dimyristoyl-PC in vesicles is very limited (unpublished observation). Our observations agree with the notion that aryl nitrenes do not easily insert into C-H bonds [20,23].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In contrast to Hu and Wisnieski [13], we have found that coupling of 12-APS-GA to dimyristoyl-PC in vesicles is very limited (unpublished observation). Our observations agree with the notion that aryl nitrenes do not easily insert into C-H bonds [20,23].…”
Section: Discussioncontrasting
confidence: 72%
“…1) ensures an anchoring of the nitrene-generating group in the membrane core by its attachment to the fatty acyl chain, while the carbohydrate moiety is meant to restrict the probe to the outer leaflet of sealed membrane systems [8][9][10]. In the case of coliphage M13 coat protein reconstituted in PC vesicles, evidence was provided that this probe coupled to the integral membrane peptides and not to the amino acid residues exposed on the outside of the bilayer [13,17]. Here we have used 12-APS-GA to identify the integral membrane proteins of human blood platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At different times, 0.5 ml of reaction mixture was removed, and the reaction was stopped by addition of 0.5 ml of ice-cold P1/NaCl. The (23). Complement-lysed cells were incubated with the photo-reagent and irradiated to effect crosslinking between inserted proteins and the radioactive photoprobe.…”
Section: Fig 1 Time Course Of Lysis (O) and C9 Binding (E) For Pnh-mentioning
confidence: 99%
“…In fact they have been shown to label only the hydrophobic tail of cytochrome b5 (Bisson et al, 1979), and none of the subunits of the hydrophilic F1 domain of the mitochondrial and the Escherichia coli ATP synthetase were cross-linked by arylazidophospholipids (Montecucco et al, 1983). Moreover, only intrinsic peptide fragments of the coliphage Ml 3 coat protein were derivatized by an azidoglycolipid probe (Hu & Wisnieski, 1979). In the case of the cytochrome oxidase subunit II and subunit b of the ATP synthetase, the precise sites of cross-linking with azidophospholipids were determined, and sequence analysis showed that none of the hydrophilic segments of these proteins were labelled (Bisson et al, 1982;Hoppe et al, 1983b).…”
mentioning
confidence: 99%